Memahami Anak dan Remaja Dengan Kasus Mogok Sekolah: Gejala, Penyebab, Struktur Kepribadian, Profil Keluarga, dan Keberhasilan Penanganan - Ampuni, Sutarimah; Andayani, Budi (Faculty of Psychology, Universitas Gadjah Mada, 2007)
This research is a case study conducted at the Unit Konsultasi Psikologi (Psycho-logical Consulting Unit) of the Faculty of Psychology, Gadjah Mada University. Five cases of school refusal on children and adolescents were studied qualitatively to examine the patterns of symptoms and causes of school refusal, the personality types, the family profiles, and the accom¬plishment of treatments applied. Data was gathered using clinical assessments including clinical observations, interview, intelligence tests (the WISC, SPM), and personality tests (the drawing tests, the Children’s Sentence Completion Tests). Symptoms of school refusal as observed from the clients include psychological – such as irritability and bad mood in the morning, as well as physiological – such as headache and diarrhea. School refusal, as seen from the cases, usually are precipitated by a negative experience at school, but roots in the frail, vulnerable nature of personality of the subjects. The clients’ personality is characterized with low self-esteem and high dependency. Four of five patients were last child and the other one was only child, suggesting that birth constellation may correlate with the incidence of school refusal on children and adolescents. The type of parenting that prolongs unhealthy attach-ment and does not promote sufficient inde-pendence may explain this correlation. Furthermore, the fact that four of five clients came from relatively problematic families may also indicate that children from such a family may have higher susceptibility to school refusal. Keywords: school refusal, school phobia